An Assessment of the Effects of Crimes on the Livelihood of the Youth in Arua City: A Case Study of Arua Central Division - Godwill Sagan (Uganda Christian University, 2025)
This Dissertation investigates the multifaceted impact of crimes on the livelihoods of youths in Arua Central Division. Crime is a pervasive issue that profoundly influences various aspects of individuals' lives, particularly among young people who are vulnerable to its effects. The study employed a mixed-methods approach to comprehensively examine the prevalence and types of crimes in the region, assess the socio-economic status and livelihoods of youths, analyze the impact of crimes on various dimensions of their well-being, and identify potential interventions to address these challenges. The findings revealed a concerning prevalence of crimes in Arua Central Division, ranging from property crimes such as theft and vandalism to violent crimes including assault and robbery. These crimes have significant repercussions on the socio-economic status, education, employment opportunities, social support networks, and mental health of youths in the area. The study highlighted the pervasive nature of crime's influence, affecting youths' economic well-being, educational attainment, employment prospects, social integration, and psychological well-being. Through a comprehensive analysis of survey data and qualitative interviews with key informants, the report provides nuanced insights into the lived experiences of youths affected by crime in Arua Central Division. It underscores the importance of addressing the root causes of crime, strengthening community resilience, and implementing evidence-based interventions to support the holistic development of youths. Policy recommendations included targeted efforts to improve education access, enhance employment opportunities, strengthen social support networks, and promote mental health awareness and support services. By shedding light on the complex interactions between crime and youths' livelihoods, this report contributes to a deeper understanding of the challenges faced by communities in Arua Central Division. It underscores the urgent need for collaborative efforts among stakeholders, including government agencies, community organizations, and civil society groups, to address the underlying factors driving crime and promote the well-being and prosperity of the youth in the region.
Undergraduate